A simple proof of the closed graph theorem - Ramm, Alexander G. (Global Journal of Mathematical Analysis, 2015)
Assume that A is a closed linear operator defined on all ofÂ a Hilbert space H. Then, A is bounded. This classical theorem is provedÂ on the basis of uniform boundedness principle. The proof is easily extended to Banach spaces.